Sistem Informasi Usaha Mikro, Kecil, Dan Menengah Berbasis Web - Jewis Jeriko Saragih; Stephen; Oloan Sihombing (CV. Utility Project Solution, 2020)
Micro, Small and Medium Enterprise (MSME) is a productive business, owned by an individual or business entity that has meet a certain condition or criteria as businessmen. Micro, small and medium enterprise (MSME) aims to grow and develop its capability to become a strong and independent business, enhance its role on regional development, providing jobs and promote economic growth.Information technology that is developing fast lately has driven acceleration in various fields of work. Newest and accurate information is needed, that is why the writer tries to design an information system website. This task intends to provide convenience who want to find out the information about all the North Sumatera (MSME) data, especially in Medan. This information system is built using PHP, MySQL, XAMPP, HTML, CSS (Cascading Style Sheets), Javascript, Sublime Text, Adobe Photoshop as layout design and Google Chrome browser. This information system can provide information on MSME products, employee data, basic tasks, vision and mission, organizational structure, galleries and contacts that users can reach if needed